Antenatal vaccination against Group B streptococcus: attitudes of pregnant women and healthcare professionals in the UK towards participation in clinical trials and routine implementation. (19th January 2018) - McQuaid, Fiona; Jones, Christine; Stevens, Zoe; Meddaugh, Gretchen; O'Sullivan, Catherine; Donaldson, Beverly; Hughes, Rhona; Ford, Carolyn; Finn, Adam; Faust, Saul N.; Gbesemete, Diane; Bedford, Helen; et al.
Abstract: Introduction: Maternal vaccination is increasingly part of antenatal care in the UK and worldwide. Trials of Group B streptococcus vaccines are ongoing. This study investigated the attitudes of pregnant women and healthcare professionals towards antenatal vaccination, both in routine care and a clinical trial setting. Material and methods: Survey of 269 pregnant women, 273 midwives/obstetricians and 97 neonatal doctors across seven sites in the UK assessing attitudes towards antenatal vaccinations, knowledge of Group B streptococcus, a hypothetical Group B streptococcus vaccine, and participation in clinical vaccine trials. Results: 68% of pregnant women intended to receive a vaccine during their current pregnancy (183/269) and 43% (of all respondents, 115/269) reported they would be very/fairly likely to accept a vaccine against Group B streptococcus despite only 29% (55/269) knowing what Group B streptococcus was. This increased to 69% after additional information about Group B streptococcus was provided. Twenty‐four percent of pregnant women reported they would be likely to take part in a clinical trial of an unlicensed Group B streptococcus vaccine. Fifty‐nine percent of maternity professionals and 74% of neonatologists would be likely to recommend participation in a Group B streptococcus vaccine trial to women, with the vast majority (>99%) willing to be involved in such a study. Incentives to take part cited by pregnant women included extra antenatal scans and the opportunity to be tested for Group B streptococcus. Conclusion: Pregnant women and healthcare professionals were open to the idea of an antenatal Group B streptococcus vaccine and involvement in clinical trials of such a vaccine. Education and support from midwives would be key to successful implementation.